Automatic Gait Recognition and its Potential Role in Counterterrorism. (1st February 2018) - Condell, Joan; Chaurasia, Priyanka; Connolly, James; Yogarajah, Patheepan; Prasad, Girijesh; Monaghan, Rachel
ABSTRACT: Closed-circuit television footage can be used to assemble an often-complex picture of an incident and aid in the identification of suspects after a crime or terrorist attack has occurred. For example, such footage allowed the police to not only identify the 7/7 London bombers but also to piece together the details of the bombers' movements prior to the attack. In the case of the London bombers little attempt was made to disguise their identities but where such identities are concealed it is possible to identify suspects based on other unique biometric characteristics such as the style of walk, referred to as gait. Gait feature–based individual identification has received increased attention from biometrics researchers. In this article, we propose a novel gait biometric methodology that could contribute to the counterterrorism effort and the identification of individuals involved in crime.